Strategi Pengembangan UMKM dalam Meningkatkan Kesejahteraan Masyarakat di Kelurahan Asamkumbang Kecamatan Medan Selayang - Nadia Nadia; Ilham Mirzaya Putra (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
ABSTRACT Micro, Small, and Medium Enterprises, known as MSMEs, are essential for boosting local economies and enhancing the well-being of communities. Asamkumbang Village has a notable growth in MSMEs, especially in the food, trade, service, and home-based industries. This research intends to examine strategies for developing MSMEs to better the welfare of the community in that area. The research utilized a qualitative method along with descriptive techniques. To gather data, the study involved detailed interviews, observations, and recording information from MSME participants and village leaders. The data analysis used the interactive model by Miles and Huberman, which includes steps such as reducing data, presenting it, and drawing conclusions. The findings reveal that the strategies for developing MSMEs consist of enhancing product quality, offering business management training, embracing digital marketing, and securing government assistance through mentoring and promotional support. These strategies positively affect community welfare, illustrated by higher household incomes, new job opportunities, improved community capabilities to satisfy basic needs, and stable family economies. Hence, pursuing sustainable development for MSMEs is an effective way to enhance community welfare locally. Keywords : MSMEs; Development Strategy; Community Welfare; Local Economy